Association of Renal and Cardiovascular Safety With DPP‐4 Inhibitors vs. Sulfonylureas in Patients With Type 2 Diabetes and Advanced Chronic Kidney Disease. Issue 2 (11th May 2021) - Yang, Chun‐Ting; Lin, Wei‐Hung; Li, Lun‐Jie; Ou, Huang‐Tz; Kuo, Shihchen
Abstract : This study assessed the effects of dipeptidyl peptidase‐4 inhibitors (DPP4is) vs. sulfonylureas (SUs) on composite renal, cardiovascular, and hospitalized hypoglycemia outcomes in type 2 diabetes (T2D) patients with advanced chronic kidney disease (CKD) who were underrepresented in previous clinical studies. The National Health Insurance Research Database was utilized. Patients with T2D and advanced CKD (stages 3b‐5) with stable use of DPP4is or SUs were identified during 2011–2015 and followed until death or December 31, 2016. The primary outcome was the composite renal outcome. Secondary outcomes included hospitalized heart failure (HHF), major adverse cardiovascular event (MACE), hospitalized hypoglycemia, and all‐cause death. Subdistribution hazard models were employed to assess treatment effects on clinical outcomes. A total of 1, 204 matched pairs of DPP4i and SU users were analyzed. Compared with SUs, DPP4is had no significant difference in the risks of the composite renal outcome, HHF, and three‐point and four‐point MACE (hazard ratios (95% confidence intervals): 1.10 (0.93–1.31), 1.11 (0.95–1.30), 0.97 (0.79–1.19), and 1.08 (0.94–1.24), respectively), but reduced risks of hospitalized hypoglycemia (0.53 (0.43–0.64)) and all‐cause death (0.71 (0.53–0.96)). In conclusion, among patients with T2D and advanced CKD, the use of DPP4is vs. SUs was associated with comparable safety profiles on renal and cardiovascular outcomes, and reduced risks of hospitalized hypoglycemia and all‐cause death. DPP4is may be preferred for patients with T2D and advanced CKD, and the regular monitoring on cardiac function remains crucial among this population who are at a higher risk of HHF.